2020
DOI: 10.1186/s40816-020-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of date palm pollen (Phoenix dactylifera) treatment on paracetamol-induced hepatorenal toxicity in rats

Abstract: Background: Consumption of plant-derived nutraceuticals and crude drugs in Arab traditional medicine is widely believed to confer beneficial effects in liver and kidney diseases. Fruits from the date palm Phoenix dactylifera L. are a rich source of nutrients and bioactive phytochemicals which possess a myriad of pharmacological effects. Herein, we examined the impact of Date Palm Pollen (DPP) aqueous suspension treatment on paracetamol (APAP) [Acetaminophen (APAP)] triggered hepatorenal damage in rats and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
3
2
0
Order By: Relevance
“…In animals treated with 500 mg/kg AEAASB and in the satellite test group, a significant decrease in relative liver weight of ASAT, ALAT, ALP, direct and total bilirubin, creatinine, serum urea, and urinary protein levels was associated with an increase of urinary creatinine, and renal clearance compared to the negative control group was noted. Results of the present study are similar to those of Al-Asmari et al [14] who showed that P. dactylifera pollen prevented the loss of functional integrity of the liver and kidney cell membrane related to paracetamol toxicity in Wistar rats by decreasing the levels of liver and kidney function markers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In animals treated with 500 mg/kg AEAASB and in the satellite test group, a significant decrease in relative liver weight of ASAT, ALAT, ALP, direct and total bilirubin, creatinine, serum urea, and urinary protein levels was associated with an increase of urinary creatinine, and renal clearance compared to the negative control group was noted. Results of the present study are similar to those of Al-Asmari et al [14] who showed that P. dactylifera pollen prevented the loss of functional integrity of the liver and kidney cell membrane related to paracetamol toxicity in Wistar rats by decreasing the levels of liver and kidney function markers.…”
Section: Discussionsupporting
confidence: 91%
“…As the damage induced by paracetamol is mainly oxidative, natural compounds with antioxidant activity could be used as alternative treatments for paracetamol-induced hepatorenal toxicity [ 6 ]. Several studies have shown the efficacy of medicinal plant extracts on paracetamol-induced toxicity, including the works of Sudip et al [ 12 ], Soliman et al [ 13 ], and Al-Asmari et al [ 14 ], which showed, respectively, the protective effects of Citrus macroptera fruit extracts, Ocimum basilicum leaves, and Phoenix dactylifera pollen on paracetamol-induced hepatorenal toxicity in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Although groups 4, 5, and 6 continued to show DOX‐induced oxidative cell injury, the AJDAE showed a clear antidotal effect on the nephrotoxicity in groups 5 and 6 only, as confirmed by the degeneration in the injury scope (score 4 was not documented; most recorded at score ≤ 2). This highlights AJDAE's protective role in combatting DOX nephrotoxicity, which is possibly due to its antioxidant, anti‐inflammatory, and regenerative impact, as confirmed in the past studies (Al‐Asmari et al, 2020; Younas et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…These markers have been found to be of great value in the assessment of clinical and experimental liver damage (23) . Increase liver enzymes and other hepatic biomarkers in ACN hepatoxicity were, also, reported in previous studies (24,25) .…”
Section: Oxidant Antioxidant and Anti-inflammatory Parameterssupporting
confidence: 81%